1999
DOI: 10.1002/oti.91
|View full text |Cite
|
Sign up to set email alerts
|

Students with disabilities in post‐secondary education: the perspectives of wheelchair users

Abstract: Changes in higher education in the United

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 10 publications
(9 reference statements)
0
18
0
Order By: Relevance
“…Studies of students with physical disabilities indicate that architectural barriers in schools and inadequate access to assisting devices, especially computers, are frequently reported as a hindrance to accessibility (Parett & VanBiervliet 1990; Korpela & Koivikko 1992; West et al 1993; Dudgeon et al 1996; Paul 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of students with physical disabilities indicate that architectural barriers in schools and inadequate access to assisting devices, especially computers, are frequently reported as a hindrance to accessibility (Parett & VanBiervliet 1990; Korpela & Koivikko 1992; West et al 1993; Dudgeon et al 1996; Paul 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, the social environment is also relevant: teachers and peers may have poor understanding of the children’s disabilities (Whitehouse et al 1989; Westbom 1992; Lightfoot et al 1999; Paul 1999). Many students with physical disabilities have less social contact with peers than non‐disabled students, which might influence learning opportunities (Blum et al 1991; Westbom 1992; Stevens et al.…”
Section: Introductionmentioning
confidence: 99%
“…1989; Westbom 1992; Lightfoot et al . 1999; Paul 1999) have described the poor understanding of the children's disabilities. Attention should be attached to collaboration between school staff and health professionals in caring for children suffering from JCA.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the interviews indicate that the disabled women students recognize higher education as an important tool for empowerment. They see university education as a vital stepping stone toward success in life (Okeke 2006;Paul 1999). In contrast to societal perceptions that disabled people are charity recipients that need pity, the interviews revealed that the disabled women are actively involved in changing their lives through among other ways acquiring an education.…”
Section: Discussionmentioning
confidence: 89%
“…This finding is consistent with findings from studies done in North America and the UK. For example, in the US, Paul (1999) reported that the disabled students recognized personal aspiration and pressures from family, peers, and friends as key motivators that influenced these students' decisions to attend university. Paul also found that the disabled students believed that post-secondary education could take them wherever they wanted to go in life (see also Fuller et al 2004).…”
Section: Discussionmentioning
confidence: 97%